2014
DOI: 10.1037/tep0000047
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the association of psychology training clinics’ collaborative research network: A study on client expectancies.

Abstract: A nationwide collaborative research netviiork has been developed by the Association of Psychology Training Clinics (APTC) to carry out research with the potential to improve services provided in training clinic settings. Six APTC member clinics participated in this inaugural study. In addition to demonstrating that the APTC research network can recruit clients for participation in multisite research and randomize enrolled participants to conditions effectively across the network, findings from this study also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 45 publications
4
44
0
Order By: Relevance
“…as well as the mean baseline OQ-45 score reported by similar training clinic studies (75.78 [SD = 24.32];Callahan & Hynan, 2005; 77.15 [SD = 25.02];Callahan et al, 2014).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…as well as the mean baseline OQ-45 score reported by similar training clinic studies (75.78 [SD = 24.32];Callahan & Hynan, 2005; 77.15 [SD = 25.02];Callahan et al, 2014).…”
mentioning
confidence: 75%
“…In line with the GEL model, it is also possible that individuals who are “fast responders” to treatment do not need more than one course of treatment to improve, leading to a longer time‐to‐response among those with a past treatment history. Importantly, previous research across a network of training clinics has found that a history of prior treatment was associated with client expectations for a longer treatment duration, which itself predicted a greater number of sessions attended as well as client severity at termination (Callahan et al, 2014). Unlike some prior research suggesting that initial severity of depressive symptoms impacts treatment outcomes (Mulder et al, 2006; Teri & Lewinsohn, 1986; Tunvirachaisakul et al, 2018), we did not find significant effects of the initial severity of either depressive or anxious symptoms, or overall distress on time to achieve change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that when clients were provided with information regarding the relationship between treatment efficacy and the number of sessions attended (i.e., that, on average, 50% of the clients showed a clinically significant change after 13-18 sessions), they were significantly less likely to drop out [52]. However, a recent study by Callahan et al [53] found that clients' pretreatment expectations regarding the duration of treatment remained unchanged after an education session. Conversely, clients' previous experiences with therapy were significantly related with the number of sessions attended and treatment outcome.…”
Section: Therapeutic Process and Proceduresmentioning
confidence: 99%
“…Psychology training clinics, where student clinicians learn to conduct therapy while receiving extensive supervision, are practice settings that have not been sufficiently explored. This gap in the literature is particularly noteworthy given that, as one research team notes, “psychology training clinics are ground zero in the training and development of professional psychologists” (Callahan et al., , p. 102). Research has also demonstrated that a majority of trainees will work with at least one client with suicidal ideation or behavior (e.g., Dexter‐Mazza & Freeman, ; Kleespies, Penk, & Forsyth, ).…”
mentioning
confidence: 99%